Effect of thinning on the relationship between mean ring density and climate in black spruce (Picea mariana (Mill.)B.S.P.). (23rd September 2017) - Franceschini, Tony; Gauthray-Guyénet, Vincent; Schneider, Robert; Ruel, Jean-Claude; Pothier, David; Achim, Alexis
Abstract: Relationships between wood density and climatic variables have generally been developed from unmanaged stands near the treeline. Using black spruce ( Picea mariana (Mill.) B.S.P. ) samples from the managed boreal zone in Canada, we investigated whether the relationship between mean ring density (MRD) and climatic variables is altered by silvicultural practices. We analysed the MRD of 10 384 growth rings from 72 trees sampled among 18 stands (nine thinned, nine controls) across Quebec, Canada. We constructed a mixed-effects model relating MRD to cambial age and ring width (RW). Model residuals (εM1 ), i.e. the difference between observed and predicted MRD, were then related to monthly temperature and precipitation of the year of ring formation and the year before. After thinning, RW slightly increased while MRD remained constant, thus lowering the strength of the relationship between MRD and RW. εM1 were positively related to spring temperatures and negatively related to summer temperatures and precipitation. No effect of thinning on the relationship between εM1 and climatic variables was observed. The sample trees grew in less limiting conditions than at the treeline so the reduced strength of the relationship between MRD and growth rate in thinned stands may result from a higher photosynthetic capacity. Such results may have implications in forest management as thinning could increase the value of black spruce wood.